2018
DOI: 10.7554/elife.38846
|View full text |Cite
|
Sign up to set email alerts
|

Sensory experience inversely regulates feedforward and feedback excitation-inhibition ratio in rodent visual cortex

Abstract: Brief (2-3d) monocular deprivation (MD) during the critical period induces a profound loss of responsiveness within binocular (V1b) and monocular (V1m) regions of rodent primary visual cortex. This has largely been ascribed to long-term depression (LTD) at thalamocortical synapses, while a contribution from intracortical inhibition has been controversial. Here we used optogenetics to isolate and measure feedforward thalamocortical and feedback intracortical excitation-inhibition (E-I) ratios following brief MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(107 citation statements)
references
References 76 publications
8
99
0
Order By: Relevance
“…Acute slice preparation For acute slice experiments, mice were deeply anesthetized with isoflurane immediately following photoconversion. After slicing in carbogenated (95% O2, 5% CO2) standard ACSF (in mM: 126 NaCl, 25 NaHCO3, 3 KCl, 2 CaCl2, 2 MgSO4, 1 NaH2PO4, 0.5 Na-ascorbate, osmolarity adjusted to 310 mOsm with dextrose, pH 7.35) (Miska et al, 2018), the 300 µm slices were immediately transferred to a warm (34 C) chamber filled with a continuously carbogenated choline-based solution (in mM: 110 Choline-Cl, 25 NaHCO3, 11.6 Na-ascorbate, 7 MgCl2, 3.1 Na-pyruvate, 2.5 KCl, 1.25 NaH2PO4, and 0.5 CaCl2, adjusted to 310 mOsm with dextrose, pH 7.35) (Ting et al, 2014). After 5 min, slices were then transferred to warm (34 C) carbogenated standard ACSF and incubated another 30 min before being moved to room temperature.…”
Section: Campari2 In Vivo Photoconversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute slice preparation For acute slice experiments, mice were deeply anesthetized with isoflurane immediately following photoconversion. After slicing in carbogenated (95% O2, 5% CO2) standard ACSF (in mM: 126 NaCl, 25 NaHCO3, 3 KCl, 2 CaCl2, 2 MgSO4, 1 NaH2PO4, 0.5 Na-ascorbate, osmolarity adjusted to 310 mOsm with dextrose, pH 7.35) (Miska et al, 2018), the 300 µm slices were immediately transferred to a warm (34 C) chamber filled with a continuously carbogenated choline-based solution (in mM: 110 Choline-Cl, 25 NaHCO3, 11.6 Na-ascorbate, 7 MgCl2, 3.1 Na-pyruvate, 2.5 KCl, 1.25 NaH2PO4, and 0.5 CaCl2, adjusted to 310 mOsm with dextrose, pH 7.35) (Ting et al, 2014). After 5 min, slices were then transferred to warm (34 C) carbogenated standard ACSF and incubated another 30 min before being moved to room temperature.…”
Section: Campari2 In Vivo Photoconversionmentioning
confidence: 99%
“…To measure intrinsic excitability, we performed whole cell recordings with an internal recording solution containing (in mM) 100 K-gluconate, 10 KCl, 10 HEPES, 5.37 biocytin, 10 Na2phosphocreatine, 4 Mg-ATP, and 0.3 Na-GTP, with sucrose added to bring osmolarity to 295 mOsm and KOH added to bring pH to 7.35 in pipettes with resistance between 4 and 8 mΩ Miska et al, 2018). Synaptic currents were blocked by adding picrotoxin (PTX), 6,7dinitroquinoxaline-2,3-dione (DNQX), and (2R)-amino-5-phosphonovaleric acid (APV) to standard ACSF to block γ-aminobutyric acid (GABA), α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA), and N-methyl-d-aspartate (NMDA) receptors, respectively.…”
Section: Intrinsic Excitability Measurementsmentioning
confidence: 99%
“…Upon training with correlated input patterns (Ocker and Doiron, 2018), imitating the baseline condition in which animals perceive normal visual inputs, the network exhibited structured spontaneous activity and developed stronger correlations within assemblies. Our model showed that decreasing thalamocortical connection strength (Miska et al, 2018) and decorrelating input patterns during MD, degraded synaptic weights and decreased firing rates and correlations. This was accompanied by a depression in excitatory synaptic weights within assemblies and overall inhibitory synaptic weights in the model.…”
Section: Discussionmentioning
confidence: 83%
“…To understand how neural circuits exploit various synaptic plasticity and homeostatic mechanisms to decrease and recover both firing rates and correlations during MD, we built a plastic recurrent network model consisting of randomly connected excitatory and inhibitory spiking neurons (Methods). Model neurons receive thalamic inputs, with thalamocortical synaptic efficacy onto inhibitory neurons set higher than onto excitatory neurons, consistent with previous experimental studies (Cruikshank et al, 2007;Ji et al, 2015;Miska et al, 2018). Neuronal and network parameters were chosen to generate in vivo-like firing rates, with excitatory neurons firing at 5 Hz and inhibitory neurons firing at 13 Hz (Hengen et al, 2013).…”
Section: Formation Of Structured Connectivity Assemblies During Trainmentioning
confidence: 99%
See 1 more Smart Citation